2009
DOI: 10.1111/j.1399-0004.2009.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

A founder TMIE mutation is a frequent cause of hearing loss in southeastern Anatolia

Abstract: Using Affymetrix 10K arrays, we searched for regions of homozygosity in 51 Turkish families including at least three members with either congenital or prelingual autosomal recessive non-syndromic sensorineural hearing loss (ARNSSNHL), and identified four families whose deafness mapped to the DFNB6 locus on 3p21 containing the TMIE gene. Mutation analysis revealed the p.R84W mutation in all four families. Screening of this mutation in 254 families with ARNSSNHL, without GJB2 mutations, revealed four additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
2
15
0
1
Order By: Relevance
“…When the regional distribution was evaluated, the highest percentage was observed in Southeastern Anatolia (10.3%). It was thought that this mutation, which was observed in exon 3, occured more commonly as a result of the founder effect in Anatolia and it was recommended that the mutation should be added to non-syndromic hearing loss screening programs in Middle Eastern populations (34). The fact that this mutation was found in a limited study group consisting of 21 families supports this recommendation.…”
Section: Variabilities Found In Patients Who Were Evaluated Using Thesupporting
confidence: 61%
See 1 more Smart Citation
“…When the regional distribution was evaluated, the highest percentage was observed in Southeastern Anatolia (10.3%). It was thought that this mutation, which was observed in exon 3, occured more commonly as a result of the founder effect in Anatolia and it was recommended that the mutation should be added to non-syndromic hearing loss screening programs in Middle Eastern populations (34). The fact that this mutation was found in a limited study group consisting of 21 families supports this recommendation.…”
Section: Variabilities Found In Patients Who Were Evaluated Using Thesupporting
confidence: 61%
“…The TMIE gene encodes a protein named transmembrane inner ear protein. The gene is composed of 4 exons in the 3p21 chromosomal region (34). The inner ear pathology observed in studies performed with mice in which the TMIE gene was affected showed that the gene was essential for maturation of sensory hair cells in the cochlea and development of steriocilia in the maturation process following a normal delivery (35).…”
Section: Variabilities Found In Patients Who Were Evaluated Using Thementioning
confidence: 99%
“…Screening revealed the same mutations as those identified in the probands in nine of nine such individuals tested. Preliminary results of mutation screening in this study have been previously reported (Sirmaci et al, 2009a(Sirmaci et al, , 2009bCengiz et al, 2010).…”
Section: Resultsmentioning
confidence: 88%
“…We found this mutation in eight of 258 unrelated families with autosomal recessive non-syndromic deafness ascertained from all parts of Turkey. The overall prevalence was 2.4%, but it was higher (10.3%) in Southeastern Turkey (Sirmaci et al, 2009a). We also showed that the haplotypes associated with this mutation are conserved and the mutation was estimated to have arisen about 1,250 years ago, quite likely in the southeastern region of the country (Sirmaci et al, 2009a).…”
Section: Mapping Of Autosomal Recessive Nonsyndromic Deafness Loci Inmentioning
confidence: 68%
“…The overall prevalence was 2.4%, but it was higher (10.3%) in Southeastern Turkey (Sirmaci et al, 2009a). We also showed that the haplotypes associated with this mutation are conserved and the mutation was estimated to have arisen about 1,250 years ago, quite likely in the southeastern region of the country (Sirmaci et al, 2009a). Interestingly, in a non-complementary family producing all deaf children, both parents, who were themselves the offspring of unrelated consanguineous parents, were autozygous for two different TMIE mutations resulting in affected allozygous children.…”
Section: Mapping Of Autosomal Recessive Nonsyndromic Deafness Loci Inmentioning
confidence: 82%